The outcome of early life status epilepticus-lessons from laboratory animals - Kubová, Hana; Mikulecká, Anna; Mareš, Pavel (Epilepsia open, 2023)
Status epilepticus (SE) is the most common neurologic emergency in children. Both clinical and laboratory studies have demonstrated that SE in early life can cause brain damage and permanent behavioral abnormalities, trigger epileptogenesis, and interfere with normal brain development. In experimental rodent models, the consequences of seizures are dependent upon age, the model used, and seizure duration. In studies involving neonatal and infantile animals, the model used, experimental design, conditions during the experiment, and manipulation of animals can significantly affect the course of the experiments as well as the results obtained. Standardization of laboratory approaches, harmonization of scientific methodology, and improvement in data collection can improve the comparability of data among laboratories.
Keywords: laboratorní zvířata; status epilepticus; Animals; zvířata; Animals, Laboratory; Seizures; modely nemocí na zvířatech; Brain; Status Epilepticus; mozek; záchvaty; Disease Models, Animal